Identity politics in Indonesia: A computer-mediated discourse analysis of hate speech in a virtual environment - Wagiati, Wagiati; Adji, Muhamad; Darmayanti, Nani; Zein, Muhammad Rifki Adinur (Universitas Mulawarman, 2025)
The study to analyze the computer-mediated hate speech discourse in a virtual environment. Social media and digital network connectivity allow for almost constant interaction and communication. Technological developments, accompanied by socio-political transformations, have become a widespread area of study for the production of hate speech. It is the subject of much academic research; however, a gap remains in the qualitative space that focuses on the form and function of the speech act. The study employs three distinct yet complementary traditions of discourse analysis to investigate hate speech, aiming to understand how social media users achieve the intended purpose of this type of speech. By examining the use of identity, impropriety, and intertextuality in examples of hate speech, this analysis identifies specific repetitive discursive techniques employed by speakers to achieve their goals. The study argues that to understand the features and styles of online communication, hate speech can be identified as a distinct genre of speech. However, this genre does not operate unchallenged: the data also reveals emergent counter-discourses in which other users engage in resisting hate speech through discursive reframing, sarcastic rebuttals, and appeals to civility norms, thereby shaping a contested digital space.